DESIGNING A CLIENT MONITORING SYSTEM TO IMPROVE TAX CONSULTANT SERVICES - Ahmad Rezza Ferdian; Bias Yulisa Geni (Universitas Lampung, 2024)
This research aims to increase the effectiveness of tax consultant services at PT Alfa Jaya Jasa by designing and implementing a web-based Client Monitoring System. Tax services that were previously carried out manually using Excel tended to be inefficient and had a high risk of errors. This system was developed using the Agile method, starting with analysis using the Unified Modeling Language (UML) approach, as well as applying PHP technology, the Laravel framework, and the MySQL database to create a system design. As a result, this system is able to integrate the process of inputting tax data, tax reporting, service bills, and verifying proof of payment for services. System implementation shows increased efficiency, reduced risk of errors, and accelerated data processing. Testing using the black box method ensures the system operates according to the specified specifications. With this new system, data management is better and service to clients is more optimal. In the future, further development may include adding features according to company needs and changes in tax regulations.